Cultural Assets in Support of Transition in the Europe and Central Asia Region : An Operational Perspective - World Bank (Washington, DC, 2014)
The purpose ofthis report is to provide guidance to the staff of the World Bank's Europe and Central Asia (ECA) Region with respect to mobilizing cultural assets to support socioeconomic development in our country and regional work programs. To this end it seeks to demonstrate how and when it makes sense for us to get involved in activities related to cultural asset mobilization. Equally important, it also indicates how and when we should leave cultural heritage activities to others. In particular, this report addresses the following questions: • What do we mean by integrating culture and cultural assets into our work? • Why may cultural assets be of importance for a development institution like the World Bank? • What is particular about the cultural assets of the ECA Region? • What lessons can be drawn from ECA's experience with interventions focused on cultural assets to date? • How should ECA staff address issues of cultural assets in the future?